3D joint T1/T1ρ/T2 mapping and water‐fat imaging for contrast‐agent free myocardial tissue characterization at 1.5T - Crabb, Michael G.; Kunze, Karl P.; Littlewood, Simon J.; Tripp, Donovan; Fotaki, Anastasia; Prieto, Claudia; Botnar, René M. (Magnetic resonance in medicine, 2025)
Purpose To develop a novel, free‐breathing, 3D joint T1$$ T_1 $$/T1ρ$$ T_{1ρ } $$/T2$$ T_2 $$ mapping sequence with Dixon encoding to provide co‐registered 3D T1$$ T_1 $$, T1ρ$$ T_{1ρ } $$, and T2$$ T_2 $$ maps and water‐fat volumes with isotropic spatial resolution in a single ≈7$$ ≈ 7 $$ min scan for comprehensive contrast‐agent‐free myocardial tissue characterization and simultaneous evaluation of the whole‐heart anatomy. Methods An interleaving sequence over 5 heartbeats is proposed to provide T1$$ T_1 $$, T1ρ$$ T_{1ρ } $$, and T2$$ T_2 $$ encoding, with 3D data acquired with Dixon gradient‐echo readout and 2D image navigators to enable 100%$$ 100% $$ respiratory scan efficiency. Images were reconstructed with a non‐rigid motion‐corrected, low‐rank patch‐based reconstruction, and maps were generated through dictionary matching. The proposed sequence was compared against conventional 2D techniques in phantoms, 10 healthy subjects, and 1 patient. Results The proposed 3D T1$$ T_1 $$, T1ρ$$ T_{1ρ } $$, and T2$$ T_2 $$ measurements showed excellent correlation with 2D reference measurements in phantoms. For healthy subjects, the mapping values of septal myocardial tissue were T1=1060±48ms$$ T_1=1060± 48\kern0.2778em ms $$, T1ρ=48.1±3.9ms$$ T_{1ρ }=48.1± 3.9\kern0.2778em ms $$, and T2=44.2±3.2ms$$ T_2=44.2± 3.2\kern0.2778em ms $$ for the proposed sequence, against T1=959±15ms$$ T_1=959± 15\kern0.2778em ms $$, T1ρ=56.4±1.9ms$$ T_{1ρ }=56.4± 1.9\kern0.2778em ms $$, and T2=47.3±1.5ms$$ T_2=47.3± 1.5\kern0.2778em ms $$ for 2D MOLLI, 2D T1ρ$$ T_{1ρ } $$‐prep bSSFP and 2D T2$$ T_2 $$‐prep bSSFP, respectively. Promising results were obtained when comparing the proposed mapping to 2D references in 1 patient with active myocarditis. Conclusion The proposed approach enables simultaneous 3D whole‐heart joint T1$$ T_1 $$/T1ρ$$ T_{1ρ } $$/T2$$ T_2 $$ mapping and water/fat imaging in ≈$$ ≈ $$ 7 min scan time, demonstrating good agreement with conventional mapping techniques in phantoms and healthy subjects and promising results in 1 patient with suspected cardiovascular disease.